The safety of influenza vaccine in clinically cured leprosy patients in China - Yi Zheng; Li Chen; Jie Zou; Zheng-Gang Zhu; Li Zhu; Jing Wan; Quan Hu (Taylor & Francis Group, 2018)
Background: Leprosy is an infectious disease caused by the bacterium Mycobacterium leprae. Influenza vaccine is an important influenza prevention strategy and the preparations used display good safety and tolerability profiles. But the safety of applying influenza vaccine on the clinical cured leprosy patients is unclear. Methods: We conducted an observational clinical study, in Wuhan between November 15, 2016 and March 1, 2017. Two groups of participants ≥50 years of age received a 0.5 ml dose of the inactivated split-virion trivalent influenza vaccine and a follow-up 28 days observation of any solicited and unsolicited adverse events. Results: A total of 134 subjects were included in the study. The total rate of reactogenicity was 5.4% [2/37] in leprosy group and 15.5% [15/ 97] in control group, the difference of reactogenicity between two groups was not significant (p = 0.1522). For solicited injection-sites adverse events (AEs), 12.4% [12/ 97] participants in the control group reported of itching, pain, erythema, swelling or induration, and no participants in leprosy group reported of any solicited injection-sites AEs. For solicited systemic AEs, 7.2% [7 / 97] participants in the control group reported of fever, malaise or headache, and 2.7% [1 / 37] participants in the leprosy group reported of fever, statistic result showed that the difference was not significant (p = 0.4438). Unsolicited AEs was reported by one male aged 76, 4 hours after vaccination administration, his plantar ulcer area began bleeding. All AEs were grade 1 or grade 2, and no recurrence of lepra reaction, AEs leading to early withdrawal from the study, or deaths were reported in this study. Conclusions: To our knowledge, the present study is the first clinical study to evaluate the safety of influenza vaccine in clinically cured leprosy patients. We concluded that clinically cured leprosy patients are relatively safe for influenza vaccine. More importantly, our study make a positive and scientific efforts to eradicate discrimination on leprosy. In our study, we described a patient with plantar ulcer undergoing bleeding for 4 hours after vaccine administration. Based on evidence we have, we interpret that this adverse event may probably associated with vaccine, and patients with ulcer and leprosy need intensive attention after vaccines administration.